Pengaruh Bauran Pemasaran Terhadap Loyalitas Konsumen Pondok Burdas Merdeka Pontianak - Fikri Alfitra; Samsuddin Samsuddin; Fita Kurniasari (Universitas Muhammadiyah Pontianak, 2018)
The purpose of this study was to determine the effect of the marketing mix on consumer loyalty of Pondok Burdas Merdeka Pontianak. The research method used in this research is quantitative method. The population in this study were all consumers of Pondok Burdas Merdeka Pontianak, with a sample of 100 consumers. Validity and reliability test results show that all items (statements) are valid and reliable. The results of the normality test show that the data is normally distributed. The results of simple linear regression analysis show the equation: Y = 0,992 + 0,593 X. The correlation coefficient test results show the R value of 0,390, so it can be concluded that the marketing mix has a low relationship with consumer loyalty of Pondok Burdas Merdeka Pontianak. The coefficient of determination test shows R2 value of 0,152 which means that 15,2% of consumer loyalty in Pondok Burdas Merdeka Pontianak is influenced by the marketing mix, while the rest (84,8%) is influenced by other variables not examined in this study. The results of the model feasibility test show that the F value is 17,540> F table 3,94. So it can be concluded that a simple linear regression model can be used to predict consumer loyalty in Pondok Burdas Merdeka Pontianak which is influenced by the marketing mix.